Handbook of Recovery in Inpatient Psychiatry - Singh, Nirbhay N.; Barber, Jack W.; Van Sant, Scott; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This handbook provides a guide for individualized, responsive, and meaningful care to patients with severe mental illness. It begins with an overview of the foundational aspects of recovery - definitions and assessment, recovery principles, recovery research, and applications of recovery principles in in inpatient psychiatry. Subsequent chapters offer in-depth analyses of provider competencies, the patient's role in personal choices and decision making, and the deeper healing goals of recovery. The handbook also offers detailed treatment modalities, including cognitive remediation, psychological and psychiatric services, nursing and occupational therapy services, peer support, and pharmacological treatment. Featured topics include: Sexuality and sexual health in the inpatient psychiatric setting. The power of stigma and the usage of SAMHSA (Substance Abuse and Mental Health Services Administration) principles to combat stigma. Legal advocacy. Self-advocacy and empowerment. Methods to enhance resilience and sustain recovery in inpatients. Common errors and solutions during the transformation to recovery-oriented systems. The Handbook of Recovery in Inpatient Psychiatry is a must-have resource for researchers, graduate students, clinicians, and related professionals/practitioners in psychology, psychiatry, social work, nursing, rehabilitation therapy, occupational therapy, physical therapy, and allied professionals in related mental health and medical disciplines. .
PART I. Principles -- Chapter 1. The Idea of Recovery -- Chapter 2. Principles for Recovery-Oriented Care -- Chapter 3. Sexuality and Sexual Health -- Chapter 4. Teaching Clinicians the Practice of Recovery-Oriented Care -- Chapter 5. Shared Decision-Making -- PART II. Practice -- Chapter 6. Inpatient Treatment Planning -- Chapter 7. Psychopharmacological Treatment -- Chapter 8. Cognitive Remediation in Mental Health -- Chapter 9. Psychiatric Services -- Chapter 10. Psychological Services -- Chapter 11. Mental Health Nursing Services -- Chapter 12. Occupational Therapy Services -- Chapter 13. Peer Support Services -- PART III. Advocacy, Resilience, and Empowerment -- Chapter 14. Self-Advocacy and Empowerment -- Chapter 15. Legal Advocacy -- Chapter 16. Stigma and Recovery -- Chapter 17. Enhancing Resilience and Sustaining Recovery -- Chapter 18. Change and Systems Transformation.
Keywords: Psychology, Clinical; Psychiatry